Search for excited leptons in e(+)e(-) collisions at root s=161 GeV - Abreu, P; Adam, W; Adye, T; Ajinenko, I; Alekseev, G; Alemany, R; Allport, P; Almehed, S; Amaldi, U; Amato, S; Andreazza, A; Andrieux, M; et al. (1997)
A search with the DELPHI detector at LEP for excited leptons (e*, μ*, τ* and v*) decaying through γ, W or Z transitions is reported. The data used correspond to an integrated luminosity of 10 pb-1 at an e+e- centre-of-mass energy of 161 GeV. The search for pair produced excited leptons established the limits me* > 79.6 GeV/c2, mμ* > 79.6 GeV/c2, mτ* > 79.4 GeV/c2 and mv* > 56.4 GeV/c2 at 95% confidence level, assuming that the SU(2) and U(1) couplings of excited leptons are in the same ratio as for normal leptons and considering both left and right-handed components. Limits corresponding to other assumptions are also given. The search for single excited lepton production established upper limits on the ratio λ/mℓ* of the coupling of the excited lepton to its mass.